Dankort payments as a timely indicator of retail sales in Denmark - Maria Carlsen; Peter E. Storgaard (Danmarks Nationalbank, 2010)
The paper examines whether electronic payments by card (Dankort) provides a useful indicator for retail sales in Denmark. Dankort transactions data is available about one week after the reference month, while the retail sales index is only published about three weeks later. We add to previous work by setting up a model for the seasonally adjusted volume index for retail sales. The extensions considered are meant to further enhance the usefulness of the nowcasting model for conjunctural analysis. The out-of-sample forecasting ability of the model compares favourably with a benchmark autoregression.
Keywords: 330; Elektronisches Geld; Einzelhandel; Dänemark